Consequences of an ecosystem state shift for nitrogen cycling in a desert stream. Issue 6 (5th April 2022) - Ribot, Miquel; Grimm, Nancy B.; Pollard, Lindsey D.; von Schiller, Daniel; Handler, Amalia M.; Martí, Eugènia
Abstract: Cessation of cattle grazing has resulted in the reestablishment of wetlands in some streams of the U.S. Southwest. Decades of cattle grazing prevented vascular plant growth in Sycamore Creek (Arizona, U.S.A.), resulting in stream reaches dominated by diatoms and filamentous green algae. Establishment of vascular plants can profoundly modify ecosystem processes; yet, the effects on nitrogen (N) cycling remain unexplored. We examined the consequences of this ecosystem state shift on N cycling in this N‐limited desert stream. We compared results from whole‐reach ammonium‐N stable isotope ( 15 NH4 + ) tracer additions conducted before (pre‐wetland state) and 13 yr after (wetland state) free‐range cattle removal from the watershed. Water column estimations showed that in‐stream N uptake and storage were higher in the pre‐wetland than in the wetland state. N turnover was also higher in the pre‐wetland state, indicating that assimilated N was retained for shorter time in stream biomass. In addition, N uptake was mostly driven by assimilatory uptake regardless of the ecosystem state considered. Water column trends were mechanistically explained by the fact that the dominant primary uptake compartments in the pre‐wetland state (i.e., algae and diatoms) had higher assimilatory uptake and turnover rates than those in the wetland state (i.e., vascular plants). Overall, results show that the shift in the composition and dominance of primary producers induced by the cessation of cattle grazing within the stream‐riparian corridor changes in‐stream N processing from a dominance of intense and fast N recycling to a prevalence of N retention in biomass of primary producers.